2014
DOI: 10.1186/1471-2458-14-928
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in social and economic factors lead to changes in drinking behavior in young adults? Findings from three waves of a population based panel study

Abstract: BackgroundSocial and economic measures in early childhood or adolescence appear to be associated with drinking behavior in young adulthood. Yet, there has been little investigation to what extent drinking behavior of young adults changes within young adulthood when they experience changes in social and economic measures in this significant period of their life.MethodsThe impact of changes in living arrangement, education/employment, income, and deprivation on changes in average weekly alcohol units of consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The relationship between smoking status and body weight serves as a primary motivation for continued smoking (6). Weight loss is often given as a rationale for starting to smoke, while weight gain is often cited as a deterrent for quitting (7, 8). The average weight gain among smokers is estimated between 4 – 5 kg, with a significant proportion of the population gaining well above this average (>15 kg in 13 – 33% of ex-smokers), making weight gain a major obstacle to smoking cessation (1, 2, 5).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between smoking status and body weight serves as a primary motivation for continued smoking (6). Weight loss is often given as a rationale for starting to smoke, while weight gain is often cited as a deterrent for quitting (7, 8). The average weight gain among smokers is estimated between 4 – 5 kg, with a significant proportion of the population gaining well above this average (>15 kg in 13 – 33% of ex-smokers), making weight gain a major obstacle to smoking cessation (1, 2, 5).…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Evidence from longitudinal studies suggests that the perception of difficulty managing changes in living arrangements and individual deprivation are associated with HAD. 50 Daily and non-daily smokers are at a greater risk for hazardous drinking and alcohol use disorders. 16,51 Smoking increases the risk for alcohol misuse and it is likely it has a causal role in this relationship.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some studies using fixed-effect models have focused on simultaneous changes in smoking, alcohol consumption, and weight [10,23]. Of note, a previous study found that socioeconomic factors influenced changes in drinking patterns, underscoring the need for interventions [24]. Fixed-effect models can be used to analyze individual behavioral changes that are important for lifestyle modification [25].…”
Section: Introductionmentioning
confidence: 99%